(Some Methodological Problems in Contemporary Research of Social Femininatives in the Serbian Language - Tomić, Svetlana (Poznańskie Studia Slawistyczne, 2021)
This work critically examines some epistemological problems of the institutionalized public knowledge of Serbian lingustics and the knowledge of the opposed groups of social and feminist linguists. It also provides attention to some relevant studies of feminine derivational sufixes in the Serbo-Croatian and Croatian language. Under consideration are some crucial methodological issues such as supporting a claim, reliability of evidence, presenting disagreement among sources, and research ethos. The research contributes to the fuller understanding of the problem of social femininatives and to enlarging the types of reference sources. It suggests the need of thorough diachronic and interdisciplinary research which would look at different centuries and show the correlation between macsculine and feminine sufixes, the chronological activisation and geographical distribution of social femininatives, their productivity, archaization and extinction, as well as the newest proposals.